2000
DOI: 10.1016/s1097-2765(00)80327-5
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-Catenin Signaling Induces the Expression and Activity of βTrCP Ubiquitin Ligase Receptor

Abstract: Beta-transducing repeat-containing protein (betaTrCP) targets the ubiquitination and subsequent degradation of both beta-catenin and IkappaB, thereby playing an important role in beta-catenin/Tcf and NF-kappaB-dependent signaling. Here evidence is presented that beta-catenin/Tcf signaling elevates the expression of betaTrCP mRNA and protein in a Tcf-dependent manner, which does not require betaTrCP transcription. Induction of betaTrCP expression by the beta-catenin/Tcf pathway results in an accelerated degrada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
172
2
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(186 citation statements)
references
References 38 publications
10
172
2
2
Order By: Relevance
“…This result is in agreement with our previous observations (Spiegelman et al, 2000). When the same Northern blot membrane was re-hybridized with HOS-speci®c probe, we observed a 4 ± 5-fold decrease in the levels of HOS message in the cells with activated Wnt/b-catenin signaling pathway (Figure 1a, middle panel).…”
supporting
confidence: 93%
See 1 more Smart Citation
“…This result is in agreement with our previous observations (Spiegelman et al, 2000). When the same Northern blot membrane was re-hybridized with HOS-speci®c probe, we observed a 4 ± 5-fold decrease in the levels of HOS message in the cells with activated Wnt/b-catenin signaling pathway (Figure 1a, middle panel).…”
supporting
confidence: 93%
“…We have recently found that the endogenous levels of bTrCP can be up regulated in some cells by the activation of the Wnt/b-catenin/Tcf signaling pathway, resulting in the activation of NF-kB-dependent transcription (Spiegelman et al, 2000). Since the pro®les of bTrCP and HOS expression may di er between various tissues and cell lines (Saitoh and Katoh, 2001;Spiegelman et al, 2001), in this study, we investigated the e ect of the Wnt/b-catenin signaling on the expression and activities of HOS.…”
mentioning
confidence: 99%
“…For instance, Conductin/Axin2, which binds to b-catenin and induces its degradation, has been shown to be a direct transcriptional target of b-catenin/TCF (Jho et al, 2002;Leung et al, 2002). The ubiquitin receptor ligase, b-TrCP, which is involved in targeting b-catenin to proteosomes, is also activated by Wnt/b-catenin signaling (Spiegelman et al, 2000). In addition, Wingless, the Wnt-1 ortholog in Drosophila, induces the direct expression of naked cuticle, which inhibits Dishevelled and blocks further signaling (Rousset et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The b-transducin repeat-containing protein (bTrCP) is an E3 ubiquitin ligase that represents a nodal point for down-regulation of b-catenin, Gli, and NF-kB levels (Liu et al 1999a;Maniatis 1999). As Wnt signaling has been shown to up-regulate bTrCP activity in a negative-feedback loop (Spiegelman et al 2000), the effect on the Hh and NF-kB signaling may be expected. Also, the Wnt pathway negatively regulates the activity of GSK3 (Cook et al 1996;Itoh et al 1998b;Taelman et al 2010), an enzyme that has been implicated in the regulation (e.g., degradation) of a large number of proteins, in addition to b-catenin (Zhou et al 2004;Xu et al 2009).…”
Section: Cross Talk With Other Pathwaysmentioning
confidence: 99%